2019
DOI: 10.1038/s42003-019-0572-6
|View full text |Cite
|
Sign up to set email alerts
|

pathCHEMO, a generalizable computational framework uncovers molecular pathways of chemoresistance in lung adenocarcinoma

Abstract: Despite recent advances in discovering a wide array of novel chemotherapy agents, identification of patients with poor and favorable chemotherapy response prior to treatment administration remains a major challenge in clinical oncology. To tackle this challenge, we present a generalizable genome-wide computational framework pathCHEMO that uncovers interplay between transcriptomic and epigenomic mechanisms altered in biological pathways that govern chemotherapy response in cancer patients. Our approach is teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Recently, pathway-based biomarker algorithms, such as pathCHEMO ( Epsi et al, 2019 ) and pathER ( Rahem et al, 2020 ), have demonstrated that discovery approaches that encompass information from biological pathways significantly outperform gene-centric methods which do not take into account pathway membership.…”
Section: Mechanism-centric Computational Approaches For Biomarker Discoverymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, pathway-based biomarker algorithms, such as pathCHEMO ( Epsi et al, 2019 ) and pathER ( Rahem et al, 2020 ), have demonstrated that discovery approaches that encompass information from biological pathways significantly outperform gene-centric methods which do not take into account pathway membership.…”
Section: Mechanism-centric Computational Approaches For Biomarker Discoverymentioning
confidence: 99%
“…In the past two decades, the advancement of high-throughput technologies has led to the discovery of genomic, transcriptomic, and epigenomic modalities involved in cancer initiation, progression, and treatment response. Multiple groups have started to effectively utilize molecular data produced by high-throughput oncology experiments to identify biomarkers of progression and therapeutic response in cancer patients ( Sorlie et al, 2001 ; Zhang et al, 2001 ; van’t Veer et al, 2002 ; Zhan et al, 2002 , 2006 ; Sotiriou et al, 2003 ; Ayers et al, 2004 ; Allen et al, 2006 ; Jain et al, 2009 ; Lim et al, 2009 ; Petty et al, 2009 ; Zhao et al, 2009 ; Carro et al, 2010 ; Lefebvre et al, 2010 ; Shaughnessy et al, 2011 ; Bae et al, 2013 ; Aytes et al, 2014 , 2018 ; Mitrofanova et al, 2015 ; Robinson et al, 2015 ; Wang et al, 2016 ; Giulietti et al, 2017 ; Heng et al, 2017 ; Hoadley et al, 2018 ; Abida et al, 2019 ; Epsi et al, 2019 ; Arriaga et al, 2020 ; Panja et al, 2020 ; Rahem et al, 2020 ). Yet, our understanding of the mechanisms involving these modalities, their upstream regulation, and effective therapeutic targeting remains incomplete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung adenocarcinoma (LUAD) is the most familiar histological type of lung cancer [3]. Although researchers have studied for decades to fight LUAD, their therapeutic effects are not ideal, with the 5-year survival rate only 17.4% [4,5]. Hence, to elevate the survival, it is momentous to discover novel molecular markers that might be beneficial for LUAD diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms behind cancer evolution are extremely complex, impeding accurate and reliable prognosis as well as effective treatment [3]. A standard existing approach to monitoring tumor progress and detecting/ascertaining the underlying mechanism is mRNA transcriptomics, which has led to a large number of significant prognostic biomarkers and therapeutic targets [4][5][6]. When combined with other omics information, such as microRNA, methylation and epigenetic data, mRNA transcriptomics has provided valuable insights into the mechanisms of lung cancers [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%